Complicated, Gastroduodenal Ulcer-Association of Hemorrhage and Perforation - Latourrette, Federico; Geninazzi, Héctor E (Cirugía del Uruguay, 1978)
The Authors present 15 cases of simultaneous or consecutive gastroduodenal hemorrhage and perforation. The frequency with which these associated forms occurs vary from 3 to 5 %, though the international Iiterature states a higher number of cases. Difficulties in diagnosis are analized because the deiayed diagnosis is due to not considering the associated forms, and therefore not looking for it in every patient who <loes not evolve in the usual way. It is also demonstrated that delay in diagnosis produces high mortality for serious complications. They consider the incidence, whether simultaneously or consecutively, as well as the anatomic varieties of the single, double or extensive ulcers which provoke them. A more radical initial approach is proposed by treating each of these complicatio'ns separately as a way of preventing further compl'ications. The logical therapeutics for the stated associated complications is the radical treatment of ulcerous conditions, gastrectomy, vagotomy and pyloroplastia o·r combinations of these. Conservative metho'ds, are discused accord to the high number of patients treated by simple closure of perforation who had to undergo further Surgery.